The Pengaruh Model Learning Cycle Type 7E untuk Meningkatkan Kemampuan Berpikir Kritis Peserta Didik Kelas VII pada Konsep Perubahan Zat Pada Kehidupan Sehari - hari - Karunia Waen, Thetia; Nestiadi, Adi; Berlian, Liska (PendIPA Journal of Science Education, 2025)
Lack of student understanding of learning materials often results in low learning outcomes. Therefore, selecting the right learning model is an important factor in achieving learning objectives, because it can help students understand the material more deeply. One approach that is considered effective and innovative is the Learning Cycle Type 7E model. This study aims to analyze the effect of implementing the Learning Cycle Type 7E model on students' critical thinking skills on the concept of Changes in Substances in Daily Life. The research method used was a quasi-experimental design with a nonequivalent control group design, which was carried out in one of the Public Junior High Schools in Serang City. The research sample was selected using a purposive sampling technique, consisting of 36 students in the experimental class and 36 students in the control class. Data collection was carried out using a test instrument in the form of HOTS (High Order Thinking Skills) questions that had passed validity and reliability tests. The results showed that the application of the Learning Cycle Type 7E model had a significant effect on improving the critical thinking skills of eighth grade students on the concept of changes in substances in daily life. Based on the results of the Independent Sample T-Test, a significance value (Sig. 2-tailed) of <0.001 was obtained, which is smaller than 0.05. In addition, the results of Group Statistics show that the average pre-test score of the experimental class was 37.54, while the control class was 34.78. Meanwhile, the average post-test score of the experimental class reached 41.51, higher than the control class which obtained an average of 36.59. These findings indicate that the Learning Cycle Type 7E model is effective in improving students' critical thinking skills.